Possible biochemical markers-predictors of severe course of infectious diseases in patients with type 2 diabetes mellitus - E. A. Karaseva; V. A. Martynov; Yu. V. Abalenikhina; N. S. Muravlyannikov (Журнал инфектологии, 2024)
Potentiation of chronic inflammation and oxidative stress by a new infectious agent in patients with type 2 diabetes mellitus can cause a severe course of the infectious disease. However, the study of the manifestations of oxidative stress in patients with hyperglycemia and infectious diseases is not widespread. This review reveals the features of the state of the antioxidant system in patients with type 2 diabetes mellitus and is devoted to identifying possible biochemical markers that predict severe infections among such patients.